The development of the ICD-11 Clinical Descriptions and Diagnostic Guidelines for Mental and Behavioural Disorders - First, Michael B (World Psychiatry, 2015)
The World Health Organization is in the process of preparing the eleventh revision of the International Classification of Diseases (ICD-11), scheduled for presentation to the World Health Assembly for approval in 2017. The International Advisory Group for the Revision of the ICD-10 Mental and Behavioural Disorders made improvement in clinical utility an organizing priority for the revision. The uneven nature of the diagnostic information included in the ICD-10 Clinical Descriptions and Diagnostic Guidelines (CDDG), especially with respect to differential diagnosis, is a major shortcoming in terms of its usefulness to clinicians. Consequently, ICD-11 Working Groups were asked to collate diagnostic information about the disorders under their purview using a standardized template (referred to as a “Content Form”). Using the information provided in the Content Forms as source material, the ICD-11 CDDG are being developed with a uniform structure. The effectiveness of this format in producing more consistent clinical judgments in ICD-11 as compared to ICD-10 is currently being tested in a series of Internet-based field studies using standardized case material, and will also be tested in clinical settings.